Maximization of Markers Linked in Coupling for Tetraploid Potatoes via Monoparental Haploids - Bartkiewicz, Annette M.; Chilla, Friederike; Terefe-Ayana, Diro; Lübeck, Jens; Strahwald, Josef; Tacke, Eckhard; Hofferbert, Hans-Reinhard; Linde, Marcus; Debener, Thomas (Frontiers in Plant Science, 2018)
Dihaploid potato populations derived from a single tetraploid donor constitute an efficient strategy to analyze markers segregating from a single donor genotype. Analysis of marker segregation in populations derived from crosses between autotetraploids is complicated by a maximum of eight segregating alleles, multiple dosages of the markers and problems related to linkage analysis of marker segregation in repulsion. Here, we present data on two monoparental dihaploid populations generated by prickle pollination of two tetraploid varieties with Solanum phureja and genotyped with the 12.8 k SolCAP single nucleotide polymorphism (SNP) array. We show that in a population of monoparental dihaploids, the number of biallelic SNP markers segregating in linkage to loci from the tetraploid donor genotype is much larger than in putative crosses of this genotype to a diverse selection of 125 tetraploid varieties. Although this strategy is more laborious than conventional breeding, the generation of dihaploid progeny for efficient marker analysis is straightforward if morphological markers and flow cytometry are utilized to select true dihaploid progeny. The level of introgressed fragments from S. phureja, the dihaploid inducer, is very low, supporting its suitability for genetic analysis. Mapping with single-dose markers allowed the analysis of quantitative trait loci (QTLs) for four phenotypic traits.